EFFECT OF FERTILIZER TYPE ON THE PRODUCTIVITY OF ELEPHANT GRASS (PENNISETUM PURPUREUM): A COMPARATIVE STUDY OF GOAT MANURE COMPOST, UREA, AND NPK ON INCEPTISOL SOIL - Gea, Indah; Saragih, Evi W; Lekitoo, Marlyn N.; Djunaedi, Muhammad (Universitas Veteran Bangun Nusantara, 2025)
Forage productivity strongly depends on appropriate fertilization strategies, particularly in the cultivation of Pennisetum purpureum (elephant grass), a key tropical livestock feed. This study aimed to compare the effects of three fertilizer types—goat manure compost, urea, and NPK—on the productivity of elephant grass grown on inceptisol soil. A Completely Randomized Design (CRD) was employed with four treatments (no fertilizer, 2 tons/ha compost, 150 kg/ha urea, and 422 kg/ha NPK) and three replications. Observed parameters included fresh biomass yield, dry matter yield, and organic matter yield. The results indicated that NPK treatment significantly outperformed others in all parameters: fresh biomass (35.27 tons/ha), dry matter (5.88 tons/ha), and organic matter (5.35 tons/ha). Urea provided moderate results, while compost did not significantly differ from the control. These findings suggest that NPK delivers readily available macronutrients, which greatly enhance vegetative growth. Nevertheless, goat manure compost holds long-term potential to improve soil structure and fertility. The study recommends integrating organic and inorganic fertilization as a sustainable approach in tropical forage production systems. Keywords: Elephant grass, NPK fertilizer, urea, goat manure, forage productivity, organic matter, vegetative growth